FEM for the Acoustic Modeling of Eigenmodes: Case of the Cultural Heritage Monument of Neoria, Crete - Papadakis, Nikolaos M.; Stavroulakis, Georgios E. (International Journal of Architectural Engineering Technology, 2022)
Eigenfrequencies inside a space significantly affect its acoustic characteristics, especially below the Schroeder frequency in the low-frequency range. In Architectural Acoustics, accurate detection and visualization of eigenmodes can be particularly useful in practical applications. One of the most important landmarks in Chania, Greece, is Neoria, a cluster of 16th-century Venetian shipyards. One existing Neoria will be converted and used as a multipurpose hall. For this objective, acoustic modeling and various measurements were performed in the space. One of the purposes of the measures and modeling was the investigation of the eigenfrequencies and the eigenmodes of the area. Finite Element Method (FEM) was used for the acoustic modeling, while the acoustic measurements were performed in various positions according to ISO 3382-1. Impulse responses were measured, and frequency responses of the space were extracted using Fourier analysis. The measurements and the acoustic modeling results show that the frequencies with the most significant effect on the area are 86.1 Hz, 150.7 Hz, and 204.6 Hz. Eigenmodes of the frequencies are visualized with the application of FEM and especially the positions of nodes and antinodes, which can be utilized appropriately for the optimum placement of absorbers and diffusers in the space.